Censorship detected in NI (Nicaragua) - Voidly (2026)
CRITICAL severity censorship detected in Nicaragua. Confidence: 65%. Data sourced from CensoredPlanet.
Censorship Incident ID: NI-2026-0001
Keywords: censorship; NI; censorship; critical